(untitled) (REVISTA NODO, 2019)
Spatial order and strengthening of community bonds, values that are pronounced as the main and achievable goal that sustains the actual efforts to rescue the public space in Mexico, and from which, are defined, not only the characteristics that institute the City and the desired Public space, but also, the parameters to catalog the spaces in abandon situations, dislocation, and, so, disabled to generate citizen shared values, an eradicable space. The present article analyzes the Rescue of Public Spaces Program to determine the Ideological Structure and the legitimate mechanisms that underlie the exposure of what determines the relationship between the denied City and the desired City.